1965
DOI: 10.1098/rspb.1965.0054
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular products of phytoplankton photosynthesis

Abstract: Following exposure in situ for periods of 3 to 24 h of samples of lake or sea waters to which 14 C-bicarbonate had been added, radioactivity was found in dissolved organic matter in the water as well as in the cells of phytoplankton. The amount in the water was between 7 and 50% of the total carbon fixed in the photic zone of the water column. This production of extracellular 14 C-labelled organic matter was found under a wide variety of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
5

Year Published

1971
1971
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(42 citation statements)
references
References 9 publications
2
34
1
5
Order By: Relevance
“…In addition, for each phytoflagellate population, a specific inverse relation holds between PER and mineral nitrogen concentration. This means that when nutrients decrease during a bloom because of phytoplankton uptake, higher quantities of photoassimilated carbon are released into the surrounding medium in agreement with Fogg's hypothesis (Fogg et al, 1965) and other studies (Ignatiades and Fogg, 1973;Iturriaga and Hoppe, 1977;Sharp, 1977;Wolter, 1982). None of these authors, however, reported a continuous relationship, probably because of heterogeneity in phytoplanktonic species composition.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In addition, for each phytoflagellate population, a specific inverse relation holds between PER and mineral nitrogen concentration. This means that when nutrients decrease during a bloom because of phytoplankton uptake, higher quantities of photoassimilated carbon are released into the surrounding medium in agreement with Fogg's hypothesis (Fogg et al, 1965) and other studies (Ignatiades and Fogg, 1973;Iturriaga and Hoppe, 1977;Sharp, 1977;Wolter, 1982). None of these authors, however, reported a continuous relationship, probably because of heterogeneity in phytoplanktonic species composition.…”
Section: Discussionsupporting
confidence: 75%
“…None of these authors, however, reported a continuous relationship, probably because of heterogeneity in phytoplanktonic species composition. As a result of such different physiological behaviour of the 3 main groups of phytoplankton succeeding each other in the Southern Bight of the North Sea, the highest PER values are not found in the most oligotrophic waters as suggested by earlier works (Fogg et al, 1965;Anderson and Zeutschel, 1970;Thomas, 1971;Berman and Holm-Hansen, 1974). Outside the bloom period, PER values are very similar in oligotrophic and eutrophic waters (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In regard to the way nutrients are derived from phytoplankton for bacterioplankton, Mommaerts commented that the values for phytoplankton excretion are decreasing through the years. The first values at the time of Fogg & Watt (Fogg et al, 1965) were up to 50 ~ of production while the most recent values from Williams and Yentsch (1976) were from 0 to 6 ~ He wondered if excretion per se exists at all. He stated that on the other hand he has indirect evidence of light lysis by phytoplankton.…”
Section: Source Of Nutrients For the Bacterioplankton?mentioning
confidence: 99%